Analisis Studi Kelayakan Bisnis pada Usaha Kuliner Risol Mayo - Astria Aulia Dewi; Resti Fauziah; Martindo Alexander; Perwito (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study analyzes the business feasibility of Risol Mayo, a modern culinary venture that combines flavor innovation with tradition. The research employs a descriptive qualitative approach, including direct interviews, observations, and data analysis. Results show that, from the market perspective, Risol Mayo has strong appeal due to its unique taste and affordable price, attracting various segments, especially students. Marketing strategies through social media, pre-order systems, and promotions within campus environments are deemed effective in reaching consumers.From a technical perspective, the production process is simple and efficient, utilizing easily accessible raw materials. The business is managed individually, demonstrating flexibility despite limited capacity. Social and economic aspects reveal positive impacts through product donations to underprivileged communities and the opening of reseller opportunities. Financially, this business generates a daily net profit of IDR 168,000 with a BC Ratio > 1, indicating its feasibility for operation. In conclusion, Risol Mayo demonstrates significant potential for growth with more structured management and innovative marketing strategies. This research offers practical insights for similar entrepreneurs in managing modern culinary businesses